Ophthalmoergonomics in Cataract Surgery (Clinical Cases) - I. G. Ovechkin; A. V. Morenko; N. I. Ovechkin; D. F. Pokrovsky (Oftalʹmologiâ, 2024)
Purpose. To examine clinical examples of the visual organ condition in patients with visually intense work (VIW) after cataract phacoemulsification (CEP) from the standpoint of ophthalmo-ergonomic indicators and “quality of life” (QOL).Methods. Clinical examples are based on observation of CEP patients after standard bilateral CEP and implantation of an intraocular lens (IOL) with an extended focal depth (“RayOne EMV”, model RAO200E, “Rayner Intraocular Lenses Limited”, Worthing, UK). Three months after the surgery on the second eye, patients underwent a comprehensive examination of their vision based on standard clinical methods (visometry, keratorefractometry, etc.), assessment of functional (objective accommodation) and ophthalmo-ergonomic (“Eye meter”, “Visual search” tests) indicators, as well as a study of QOL (according to the “FEC-22” questionnaire). The article presents two clinical examples, each of which comparatively discusses the examination data of two VIW patients — air traffic controllers.Results. The first clinical example presents a significant (15.9 %) deterioration in visual performance (VP) according to the “Eye meter” test under conditions of a deficit (3 sec) of time for presenting the test task, which is associated with the patient’s anisometropia (0.2 relative units). The second example presents a decrease (20.8 %) in VP according to the “Visual search” test due to the patient’s impaired accommodative function of the eye (habitual excessive accommodative tension). In both cases, the identified dynamics are accompanied by a decrease in the QOL indicator (by 3.7–5.8 %, respectively) according to the “FEK-22” questionnaire, which is associated with the methodological features of the development of this questionnaire.Conclusion. Conducting an ophthalmo-ergonomic examination in cataract surgery reflects the “social model” of health, which considers limitations of life activity as a social problem and, therefore, the goal of treatment is the complete integration of the individual into society or, in other words, preserving the “professional” vision of the VIW patient and continuing (after surgery) everyday visual activity with the required indicators of visual performance. Ophthalmo-ergonomic indicators closely related to the patient’s QOL allow us to determine the “reference points” for conducting the necessary set of therapeutic and preventive measures to preserve the “professional” vision of the VIW patient.